MENINGKATKAN HASIL BELAJAR SEPAK BOLA MELALUI PERMAINAN GAWANG TONG PADA SISWA KELAS V SD - Rabuansyah, Rabuansyah; Haetami, Mimi; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is whether the goalkeeper game can improve the learning outcomes of soccer students of class V SDN 39 Sungai Kakap. The purpose of this research is to know the improvement of learning result of soccer through goalkeeper game in class V student of SDN 39. This research method with type of classroom action research. The subjects of this research are students of class V SDN 39 Sungai Kakap Kubu Raya as many as 11 students consisting of 3 sons and 8 daughters. The results obtained from this study are 1. On the aspect of student understanding in the cycle 68.21% cycle 76.43% and cycle II 87.50% has increased 2. Aspects of observation on the average pre cycle 65.00%, cycle I 76.67%, and cycle II average reach 90%. Â Keywords: Football, goalkeeper and game approach method.